1998
DOI: 10.1017/s0954102098000091
|View full text |Cite
|
Sign up to set email alerts
|

FT-Raman spectroscopic analysis of endolithic microbial communities from Beacon sandstone in Victoria Land, Antarctica

Abstract: Laser-based Fourier-Transform Raman spectroscopy (FTRS) has been used to identify in situ compounds of ecophysiological significance in diverse field-fresh Antarctic cryptoendolithic microbial communities. FTRS does not disrupt the community and permits characterization of visible and invisible compounds in their natural configuration within cells and their current or former microhabitat. The small "footprint" of the microscopic laser beam permits accurate analysis of discrete zones of compounds produced by ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 16 publications
2
68
0
Order By: Relevance
“…In another case of salinixanthin from S. ruber Raman spectra indicate that there are few structural differences [52]. Other studies also demonstrated in laboratory conditions that benchtop instrumentation is able to detect biomolecules associated with the extremophilic endolithic colonization of rocks [38,[53][54][55][56][57][58][59][60].…”
mentioning
confidence: 96%
“…In another case of salinixanthin from S. ruber Raman spectra indicate that there are few structural differences [52]. Other studies also demonstrated in laboratory conditions that benchtop instrumentation is able to detect biomolecules associated with the extremophilic endolithic colonization of rocks [38,[53][54][55][56][57][58][59][60].…”
mentioning
confidence: 96%
“…The cryptoendolithic habitat is widespread throughout the Beacon Supergroup, extending from Victoria Land through the Transantarctic Mountains, East Antarctica (Russell et al 1998). The samples were collected by a British Antarctic Survey expedition to Terra Nova Bay and McMurdo Base during the Antarctic summer of 1995-1996(Edwards et al 1997, from six different localities (Table 1 and Fig.…”
Section: Specimensmentioning
confidence: 99%
“…Inorganic compounds of ecological significance such as UV screening haematite and bio-weathering calcium oxalate have similarly been studied using laser Raman spectroscopy. Calcium oxalate can be detected as evidence of rock bioweathering (Russell et al 1998). The Raman water signature is small so that it is applicable to untreated field-fresh material.…”
Section: Laser Raman Spectroscopymentioning
confidence: 99%
“…For studies of Antarctic samples of cryptoendolithic microorganisms, spectra were recorded using a Fourier transform (FT) Bruker IFS66 (Bruker IR Analytische GmbH, Karlsruhe) laboratory instrument and FRA 106 Raman module attachment with 350 mW Nd/YAG laser excitation at 1064 nm and a liquid nitrogen-cooled germanium detector (Russell et al 1998 ;Newton et al 2000). For spectroscopy of rock profiles and surface crusts, this was coupled via a TV camera to a Raman microscope with a r40 objective giving a spot diameter of y40 mm at the sample.…”
Section: Laser Raman Spectroscopymentioning
confidence: 99%